The 2011 Van Earthquake s and Resilience in the Urban Population - Jae Hun Choi; Faruk Alaeddinoğlu (Coğrafya Dergisi)
About a decade after the 2011 earthquakes, can people say that the city of Van has recovered now? This study purposes to answer this question by presenting a method for measuring the shock and process of recovering from an earthquake in terms of resilience and to provide objective results indicating whether or not Van has recovered from the shock of the 2011 earthquakes using this method. This study presents a method for measuring resilience in terms of population and local economic resilience. This study proposes the following five variables for measuring resilience in terms of population: d ecline year, drop (the degree of decline than expected), rebound (the velocity of recovery from decline), resilience index, and slope change (of the population regression equation). By synthesizing the resilience measurement results up to the end of 2019, the population growth rate of the whole city has yet to return to pre-earthquake levels. When measuring the resilience indicators at the neighborhood level, the neighborhoods that Housing Development Administration of Türkiye (TOKİ) had built and the neighborhoods around the city center show high resilience. The resilience indicators for neighborhoods near TOKİ were low. The conclusion is that appropriate measures have not been taken from the perspective of the entire city of Van to overcome the effects of the 2011 earthquakes.